К изучению фауны трематод воробьиных птиц Украины - Искова, Н.И. (Вестник зоологии, 1971)
Trematode of the passeriform birds of the Ukraine were almost unstudied lill re cently. Altogether in the territory of the Ukraine there were known 11 species of trema tode from 9 passeriform birds 'out of 123 known for the Ukrainian fauna. By means of complete helminthological dissection 381 individuals of 57 species <>l passeriform birds were investigated from different regions of the Ukraine. Treniatode were found in 61 individuals (16.01%). Altogether 27 species of trematode were found belonging to 12 genera of 7 families. Out of them 11 species are given first for tile III; rainian fauna, one of them proved to be new for science.